Mutations in GET4 disrupt the transmembrane domain recognition complex pathway. - Tambe, Mitali A; Ng, Bobby G; Shimada, Shino; Wolfe, Lynne A; Adams, David R; Gahl, William A; Bamshad, Michael J; Nickerson, Deborah A; Malicdan, May C V; Freeze, Hudson H (J Inherit Metab Dis, 2020)
The transmembrane domain recognition complex (TRC) targets cytoplasmic C-terminal tail-anchored (TA) proteins to their respective membranes in the endoplasmic reticulum (ER), Golgi, and mitochondria. It is composed of three proteins, GET4, BAG6, and GET5. We identified an individual with compound heterozygous missense variants (p.Arg122His, p.Ile279Met) in GET4 that reduced all three TRC proteins by 70% to 90% in his fibroblasts, suggesting a possible defect in TA protein targeting. He presented with global developmental delay, intellectual disabilities, seizures, facial dysmorphism, and delayed bone age. We found the TA protein, syntaxin 5, is poorly targeted to Golgi membranes compared to normal controls. Since GET4 regulates ER to Golgi transport, we hypothesized that such transport would be disrupted in his fibroblasts, and discovered that retrograde (but not anterograde) transport was significantly reduced. Despite reduction in the three TRC proteins, their mRNA levels were unchanged, suggesting increased degradation in patient fibroblasts. Treating fibroblasts with the FDA-approved proteasome inhibitor, bortezomib (10 nM), restored syntaxin 5 localization and nearly normalized the levels of all three TRC proteins. Our study identifies the first individual with GET4 mutations.